1989
DOI: 10.1083/jcb.109.1.285
|View full text |Cite
|
Sign up to set email alerts
|

Induction of in vitro differentiation of mouse embryonal carcinoma (F9) and erythroleukemia (MEL) cells by herbimycin A, an inhibitor of protein phosphorylation.

Abstract: Abstract. Herbimycin A is one of the benzenoid ansamycin antibiotics isolated from a culture of a Streptomyces species (Omura, S., A. Nakagawa, and N. Sadakane. 1979. Tetrahedron Lett. 1979 164: 294-298). These studies and other evidence indicate that the antibiotic inhibits a reaction(s) closely associated with the function of cellular tyrosine kinases.We have found that herbimycin A is an effective inducing agent capable of triggering differentiation in two typical mouse in vitro differentiation systems, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To examine whether this is the case, HA, a known inhibitor of non‐receptor type PTK (e.g. Honma et al 1989 ; Kondo et al 1989 ) was used to see whether PMC migration was interfered with to any extent. By treating unhatched embryos with 10 μg/mL HA for 5 h, embryos reached the early mesenchyme blastula stage.…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether this is the case, HA, a known inhibitor of non‐receptor type PTK (e.g. Honma et al 1989 ; Kondo et al 1989 ) was used to see whether PMC migration was interfered with to any extent. By treating unhatched embryos with 10 μg/mL HA for 5 h, embryos reached the early mesenchyme blastula stage.…”
Section: Resultsmentioning
confidence: 99%
“…A number of pro- teins contribute to the multiple cytoskeletal proteins concentrated at focal adhesions (Owens et al, 1995). Focal adhesion proteins have been categorized as either structural molecules, such as the actin-binding proteins tensin and vinculin, or regulatory molecules, including focal adhesion kinase (FAK) and paxillin (Kondo et al, 1989;Wood et al, 1994). Our results demonstrated that in RL95-2 cells retinoic acid did not cause changes in phosphorylation of FAK (data not shown), a protein with a molecular weight of 125 kDa, although actin filaments were reorganized.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced activity of protein tyrosine kinases has been implicated in the establishment and progression of many cancers and other diseases (Levitzki and Gazit, 1995). Inhibition of protein tyrosine kinases causes actin filament reorganization (Kwon et al, 1995) and differentiation of erythroid, mouse embryonal carcinoma (F9) and human leukemia cells (Kondo et al, 1989;Honma et al, 1989). Tyrphostins inhibit several tyrosine kinases (Levitzki and Gazit, 1995) while inducing differentiation of mouse erythroleukemic cells (Anafi et al, 1993b).…”
mentioning
confidence: 99%